2018
DOI: 10.1002/wps.20492
|View full text |Cite|
|
Sign up to set email alerts
|

Income inequality and depression: a systematic review and meta‐analysis of the association and a scoping review of mechanisms

Abstract: Most countries have witnessed a dramatic increase of income inequality in the past three decades. This paper addresses the question of whether income inequality is associated with the population prevalence of depression and, if so, the potential mechanisms and pathways which may explain this association. Our systematic review included 26 studies, mostly from high-income countries. Nearly two-thirds of all studies and five out of six longitudinal studies reported a statistically significant positive relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
261
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 361 publications
(311 citation statements)
references
References 55 publications
15
261
0
5
Order By: Relevance
“…Negative affectivity and self‐control are especially important, given the prospective significance of early‐onset phobia, hyperactivity and oppositional‐defiant behavior. Also of interest, but less thoroughly investigated, are the mental health effects of distal socio‐economic and cultural factors, such as inferior social status, income inequality, migration, and their effect mediators.…”
mentioning
confidence: 99%
“…Negative affectivity and self‐control are especially important, given the prospective significance of early‐onset phobia, hyperactivity and oppositional‐defiant behavior. Also of interest, but less thoroughly investigated, are the mental health effects of distal socio‐economic and cultural factors, such as inferior social status, income inequality, migration, and their effect mediators.…”
mentioning
confidence: 99%
“…First, in the full range of rural, peri‐urban, and urban areas, availability of crops and animals for household consumption can provide food security (Ayenew et al, ; Sen, ) which, in turn, has shown associations with improved mental health (Weaver & Hadley, ). More indirectly, livestock and land can contribute to the household income, which also has shown associations with improved mental health (Berinyuy & Fontem, ; Burns, Tomita, & Lund, ; Fone et al, ; Hruschka et al, ; Vikram Patel et al, ; Pickett & Wilkinson, ). Beyond such direct effects on food security, nutrition, and income, success in agricultural activities might also enhance social capital and status to provide further buffering effects for mental health (Glass et al, ; Grabe et al, ; Hoke, ; Nanama & Frongillo, ; Pike & Patil, ; Rao, ).…”
Section: Discussionmentioning
confidence: 99%
“…Determining which questions have value is more challenging, since allocating resources to any priority comes at the cost of divesting them from alternatives. For example, the focus on mechanistic approaches to psychological treatments could distract from other, pervasive determinants of mental disorders, like poverty (Deighton, et al, 2019), income inequality (Patel, et al, 2018) or living in a conflict zone (Jayasuriya, Jayasuriya, Tay, & Silove, 2016). Specifically, proposing a simple behavioral intervention like the Tetris game to tackle intrusive memories in refugees from warzones like Syria (Holmes, et al, 2017) might deflect from the disabling and enduring consequences of war-related trauma (Silove, et al, 2014).…”
Section: Are Research Decisions Based On Questions Relevant To Usersmentioning
confidence: 99%